2019
DOI: 10.1111/1475-6773.13192
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining the HIV care provider workforce: Medical Monitoring Project HIV Provider Survey, 2013‐2014

Abstract: Objective To describe delivery of recommended HIV care and work satisfaction among infectious disease (ID) physicians, non‐ID physicians, nurse practitioners (NPs), and physician assistants (PAs). Data Sources Medical Monitoring Project 2013‐2014 HIV Provider Survey. Study Design Population‐based complex sample survey. Data Collection/Analysis Methods We surveyed 2208 HIV care providers at 505 US HIV care facilities and computed weighted percentages of provider characteristics, stratified by provider type. Rao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…22 In addition to this finding, a previous MMP analysis found that NPs were twice as likely as ID physicians to report providing comprehensive sexual behavior-related risk-reduction services. 8 There are several potential explanations for our finding that patients of ID physicians were less likely than others to be retained in care. It is possible that patients of ID physicians on average require less frequent visits than patients of other provider types because of lower medical complexity due to having fewer comorbidities or differing social determinants of health for which we did not control.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…22 In addition to this finding, a previous MMP analysis found that NPs were twice as likely as ID physicians to report providing comprehensive sexual behavior-related risk-reduction services. 8 There are several potential explanations for our finding that patients of ID physicians were less likely than others to be retained in care. It is possible that patients of ID physicians on average require less frequent visits than patients of other provider types because of lower medical complexity due to having fewer comorbidities or differing social determinants of health for which we did not control.…”
Section: Discussionmentioning
confidence: 95%
“…8 Another analysis of MMP data found that among patients who needed HIV case management, those who received care from ID physicians were more likely than patients of NPs to have that need remain unmet, even after accounting for patient differences and the availability of onsite HIV case management services at the HIV care facility (publication pending), suggesting that coordination of care may more often be lacking among some patients of ID physicians with complex needs. In addition, a 2014 MMP survey of HIV care providers found that NPs are more likely than ID physicians to provide care for .50 HIV patients and are 5 times as likely to be full-time HIV care providers, 8 which aligns with previous findings that experience, rather than provider profession, is associated with favorable outcomes. [18][19][20] Retention in care and recommended STI testing are dependent on the coordination of care and prevention elements of primary care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations